World Economic Outlook, April 1985. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1985)
This paper highlights that the performance of the world economy in 1984 turned out to be considerably better than had been expected at the beginning of the year. Output grew robustly in the industrial countries, especially in the United States and Japan; inflation continued to decline; and developing countries saw a noteworthy improvement both in their balance-of-payments position and in their domestic growth performance. Fears that the debt situation might deteriorate did not materialize.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet